Environmental-economic analysis of integrated organic waste and wastewater management systems: a case study from Aarhus City (Denmark) - Thomsen, Marianne; Romeo, Daina; Caro, Dario; Seghetta, Michele; Cong, Rong-Gang (MDPI, 2018)
This study presents a comparative analysis of the environmental and economic performances of four integrated waste and wastewater management scenarios in the city of Aarhus in Denmark. The purpose of this analysis is to deliver decision support regarding whether (i) the installation of food waste disposers in private homes (AS1) or (ii) separate collection and transport of organic waste to biogas plants is a more viable environmental and economic solution (AS2). Higher environmental benefits, e.g., mitigation of human health impacts and climate change, are obtained by transforming the existing waste combustion system into scenario (ii). Trade-offs in terms of increased marine eutrophication and terrestrial ecotoxicity result from moving up the waste hierarchy; i.e., from waste incineration to biogas production at wastewater treatment plants with anaerobic sludge digestion. Scenario (i) performs with lower energy efficiency compared to scenario (ii). Furthermore, when considering the uncertainty in the extra damage cost to the sewer system that may be associated to the installation of food waste disposers, scenario (ii) is the most flexible, robust, and less risky economic solution. From an economic, environmental, and resource efficiency point of view, separate collection and transport of biowaste to biogas plants is the most sustainable solution.
Keywords: LCA; CBA; organic household waste; wastewater; circular resource management systems